2021
DOI: 10.1371/journal.pone.0262017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of micro-RNA in extracellular vesicles from blood of patients with prostate cancer

Abstract: Extracellular vesicles (EVs) contain various types of molecules including micro-RNAs, so isolating EVs can be an effective way to analyze and diagnose diseases. A lot of micro-RNAs have been known in relation to prostate cancer (PCa), and we evaluate miR-21, miR-141, and miR-221 in EVs and compare them with prostate-specific antigen (PSA). EVs were isolated from plasma of 38 patients with prostate cancer and 8 patients with benign prostatic hyperplasia (BPH), using a method that showed the highest recovery of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…Exosomes containing miRs, secreted by cancer cells, can be internalized by neighboring or distant recipient cells, facilitating tumor development [ 18 ]. The miRs from the miR-15/16 cluster are acknowledged as tumor suppressors, with documented reductions in various cancers, such as chronic lymphocytic lymphoma [ 66 ], pituitary adenomas [ 67 ], and PC [ 68 ]. Consistent with prior research, we observed a significant downregulation of serum exosomal miR-15a and miR-16 (fold regulation of −2.00 and −3.24, respectively) in mCRPC patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exosomes containing miRs, secreted by cancer cells, can be internalized by neighboring or distant recipient cells, facilitating tumor development [ 18 ]. The miRs from the miR-15/16 cluster are acknowledged as tumor suppressors, with documented reductions in various cancers, such as chronic lymphocytic lymphoma [ 66 ], pituitary adenomas [ 67 ], and PC [ 68 ]. Consistent with prior research, we observed a significant downregulation of serum exosomal miR-15a and miR-16 (fold regulation of −2.00 and −3.24, respectively) in mCRPC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our study, Damodaran et al (2021) revealed a significant downregulation of miR-21 in PC patients [ 84 ]. Conversely, Kim et al (2021) reported no significant alterations in miR-21 and miR-141 levels in extracellular vesicles of PC patients compared to the control group [ 68 ]. Our investigation shows a decreased expression of serum exosomal miR-21 levels in mCRPC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes containing miRs, secreted by cancer cells, can be internalized by neighboring or distant recipient cells, facilitating tumor development [16]. The miRs from the miR-15/16 cluster are acknowledged as tumor suppressors, with documented reductions in various cancers, such as chronic lymphocytic lymphoma [64], pituitary adenomas [65], and prostate cancer [66]. Consistent with prior research, we observed a significant downregulation of serum exosomal miR-15a and miR-16 (fold regulation of -2.00 and -3.24, respectively) in mCRPC patients.…”
Section: Discussionmentioning
confidence: 99%
“…To identify miRNAs as potential biomarkers, first, it is necessary to identify their specific expression profile in the tissue of patients with and without PCa, thus attributing this deregulation to the carcinogenic events that occur in the prostate and evaluating whether these miRNAs conserved the differential expression in some body fluid and whether this is related to their expression in the specific tissue. In addition, numerous studies have reported the utility of miRNAs for disease detection and prognosis ( Byun et al, 2022 ; Giglio et al., 2021 ; Kim et al, 2021 ; Lyu et al, 2019 ; Porzycki et al, 2018 ; Suer et al, 2019 ). miRNAs miR141-3p ( Osipov et al, 2016 ; Xiao et al, 2012 ), miR145-5p ( Wang et al, 2015 ; Xu et al, 2019 ), miR146a-5p ( Fredsøe et al, 2020 ; Huang et al, 2017 ), and miR148b-3p ( Feng et al, 2019 ; Tomeva et al, 2022 ; Walter et al, 2013 ) have been suggested as predictive molecules for cancer, and especially in PCa for their role in carcinogenesis, tumor progression, and metastasis.…”
Section: Introductionmentioning
confidence: 99%